PENGARUH KESADARAN MERK, PERSEPSI KUALITAS, DAN LOYALITAS MERK TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE VIVO PADA ANGKASA CELL DI KOTA SEMARANG - Ana Putri Nastiti; Diva Riza Fahlefi (Sekolah Tinggi Ilmu Ekonomi Semarang, 2019)
The increasing competition between similar products, the companies compete with each other to win over consumers. The purpose of this study was to find out whether brand awareness, perceived quality of brand loyalty towards the purchase decision of the Vivo handphone on the cell space in Semarang Regency. The population in this study were all customers or consumers who used or made mobile phone purchasing decisions on space cells in Semarang Regency, totaling 154 customers. purpose sampling, namely the selection of samples based on certain characteristics to 63 respondents. The method of data analysis uses multiple linear regression, coefficient of determination and hypothesis testing. The results of this study show that the regression coefficient value of brand awareness is 0.301, tcount (3.958)> t table (1.66) and sign (0.000) <(0.05) means that brand awareness has a positive and significant influence on purchasing decisions. The qualification perception regression coefficient value is 0.303. tcount (3.694)> t table (1.66) and sign (0,000) <(0.05), meaning that the perception of quality has a positive and significant influence on purchasing decisions. The regression coefficient value Brand loyalty is 0.242. tcount (3,438)> t table (1,66) and sign (0,001) <(0,05), means that brand loyalty has a positive and significant influence on purchasing decisions. Brand awareness, Perception of Brand Loyalty Quality together - have a positive and significant effect on purchasing decisions, this is evidenced in the F test which obtained F count of 37.095 and signification value of 0.000 <0.05. Determination Coefficient test results R2 is 0.616 means brand awareness, Perception Quality Brand loyalty has the role of 61.6%, together - able to explain the purchase decision variables, while the remaining 64.2% explained other variables. Based on the results of research on the purchase decision of Vivo cellphones in space cells in Semarang Regency in the medium category, and approved to increase brand awareness offered, thus increasing consumer confidence in cellphones on cellular phones